2014
DOI: 10.1111/vde.12115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of tromethamine edetate disodium dihydrate on antimicrobial susceptibility of Pseudomonas aeruginosa in biofilm in vitro

Abstract: Triz-EDTA(®) may be a useful adjunctive treatment for chronic cases of Pseudomonas otitis where biofilms may have developed, if gentamicin or neomycin is to be used as a topical treatment. In vivo study is required to confirm this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…neomycin, streptomycin, kanamycin, spectinomycin, gentamicin and tobramycin), erythromycin and imipenem can lead to antagonism against various bacterial strains, including P. aeruginosa (Goswami & Jawali, ; Parry & Neu, ; Rodríguez‐Beltrán et al, ; Saggers & Lawson, ). Likewise, when Tris‐EDTA combined with enrofloxacin against P. aeruginosa canine otic isolates ( n = 31), there was a reduction in antibacterial efficacy with fourfold or higher MIC in 39% of the isolates (Pye et al, ). However, we have shown in a previous study (in press) that such antagonism does not occur when NAC or Tris‐EDTA is combined with ionophores (Chan et al, in press).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neomycin, streptomycin, kanamycin, spectinomycin, gentamicin and tobramycin), erythromycin and imipenem can lead to antagonism against various bacterial strains, including P. aeruginosa (Goswami & Jawali, ; Parry & Neu, ; Rodríguez‐Beltrán et al, ; Saggers & Lawson, ). Likewise, when Tris‐EDTA combined with enrofloxacin against P. aeruginosa canine otic isolates ( n = 31), there was a reduction in antibacterial efficacy with fourfold or higher MIC in 39% of the isolates (Pye et al, ). However, we have shown in a previous study (in press) that such antagonism does not occur when NAC or Tris‐EDTA is combined with ionophores (Chan et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiofilm activities of commercial antiseptics such as Octenillin ® , Prontosan ® and Betadine ® against S. aureus and P. aeruginosa biofilms increased by 20,000‐fold, 4000‐fold and 200‐fold, respectively in the presence of EDTA (Lefebvre, Vighetto, Di Martino, Garde, & Seyer, ). Pye, Singh, and Weese () demonstrated that Triz‐EDTA ® aqueous flush increased the susceptibility of P. aeruginosa biofilms (MIC 90 ) to gentamicin by 16‐fold and neomycin by twofold in cases of canine OE. Hence, further study is warranted to test the combination of Tris‐EDTA or disodium EDTA with other antimicrobial agents for the presence of synergistic antibiofilm activity.…”
Section: Discussionmentioning
confidence: 99%
“…Otitis is believed to be multifactorial and treatment can be difficult in some cases. [1][2][3] Common organisms isolated from dogs with otitis externa include Staphylococcus spp., Pseudomonas spp., Proteus spp., Streptococcus spp., Escherichia coli, Klebsiella spp., Bacteroides spp., Pasteurella spp. and Malassezia spp.…”
Section: Introductionmentioning
confidence: 99%
“…As for carbapenems, it is rather striking to detect 2% resistance in reptile strains as their canine and feline parallels were all sensitive according to current literature [8]. Although polymyxin B resistance was once reported in canine P. aeruginosa [9], there exists no direct evidence to implicate colistin (also known as polymyxin E) resistance that was expressed by almost 50% of snake isolates in our study. Combined, to our knowledge, P. aeruginosa from snakes' oral cavity are highly antibiotic-resistant.…”
Section: Discussionmentioning
confidence: 57%